Cephalopod fishery and population dynamics ofLoligo duvauceli (Orbigny) off Saurashtra region,Gujarat - Thomas, Sujitha; Kizhakudan, Shoba Joe (Indian Journal of Fisheries, 2011)
The fishery of cephalopods and some aspects of population dynamics ofÂ  theIndian squid Loligo duvauceli from Veraval and Mangrol in Saurashtra regionwas studied for the period 1996-99. The average annual landing of cephalopodsby trawl in Veraval and Mangrol were estimated at 3911t and 1030t respectively,which contributed 4.8 and 5.7% of the total fish landings in Veraval and Mangrol.Loligo duvauceli dominated the catch (58%) , followed by Sepia aculeata (19%),S. elliptica (19%), S.pharaonis (3%) and Sepiella inermis (1%). The length weightrelationship was estimated for males and females of Loligo duvauceli as W=0.109011 L 2.634609 and W = 0.314656 L 2.185796 respectively. The estimates of VBGFparameters were L! = 303mm and K= 0.98 year -1. The mortality rates values Z,M, F were 3.94, 1.94 and 2.20 respectively. The exploitation rate was 0.56. Thepresent study shows that the resource is exploited above the optimum level andthe effort has to be reduced for sustaining the resource for long term exploitation.